Unsteady two-layered fluid flow and heat transfer of conducting fluids in a channel between parallel porous plates under transverse magnetic field - Linga Raju, Temburu; Nagavalli, Madhupada (Zielona Góra: Uniwersytet Zielonogórski)
The unsteady magnetohydrodynamic flow of two immiscible fluids in a horizontal channel bounded by two parallel porous isothermal plates in the presence of an applied magnetic and electric field is investigated. The flow is driven by a constant uniform pressure gradient in the channel bounded by two parallel insulating plates, one being stationary and the other oscillating, when both fluids are considered as electrically conducting.
Keywords: magnetohydrodynamics; two-layered fluid flow/immiscible fluids; unsteady flow; oscillatory motion; heat transfer; porous plates